A new method for locating and quantifying damage in beams from static deflection changes. (1st February 2019) - Le, N.T.; Thambiratnam, D.P.; Nguyen, A.; Chan, T.H.T.
Highlights: Closed form functions of static deflection change ( DC ) due to damage was developed. The static DC follows certain patterns that clearly reveal the damage location. Linear relationship between the relative DC and a damage severity derivative was developed. A new damage quantification concept named damage-severity-consistency function was proposed. The proposed method was comprehensively validated both numerically and experimentally. Abstract: This paper presents a new method that can locate and quantify damage in Euler-Bernoulli beams from changes in static deflection. Using the principle of Virtual Work, for the first time, the deflection change ( DC ) parameter is formulated as a function of both the damage location and damage severity. Through this, the study shows that the changes in static deflection follow certain patterns that clearly reveal the damage location. Therefore, by observing a plot of the measured DC, the damage locations can be identified conveniently. Once the damage is located, its severity is estimated directly from the measured relative deflection change through a new concept named damage severity consistency ( DSC ) function. A constant or nearly constant DSC function indicates a high precision of the damage detection results and reflects a good quality of the measurement data. Numerical and laboratory investigations demonstrate that the method accurately locates and quantifies the damage under various scenarios in statically determinate beams. The proposed damage detection method has a clear theoretical base, does not rely on an optimization algorithm, and can be extended to other beam-type structures including statically indeterminate beams.